Psychological experiences of women with pregnancy termination due to fetal anomalies: a qualitative study from the perspective of women, their spouses, and healthcare providers in Iran - Bahareh Kamranpour; Mahnaz Noroozi; Masoud Bahrami (BMC, 2020)
Abstract Background Pregnancy termination due to fetal anomalies has many psychological consequences for women. Providing appropriate and desirable care to this group of women and their families plays an important role in the process of coping with this crisis. The aim of the present study was to explore the psychological experiences of women with pregnancy termination due to fetal anomalies. Methods This was a qualitative content analysis study. 40 participants were selected through purposeful sampling with maximum variation and data were collected through in-depth individual interviews, field notes, and analyzed using the conventional qualitative content analysis method simultaneously. Results After analyzing the interview transcripts, the psychological experiences of women with pregnancy termination due to fetal anomalies were classified into two main categories: "emotional reactions coinciding with the diagnosis of fetal anomalies" (consisting of two sub-categories of "disbelief and denial of fetal anomalies" and "feelings of sadness and anger") and " psychological problems following pregnancy termination" (consisting of two sub-categories of " feeling helpless, fearful, anxious, and depressed" and "feeling conscience-stricken, and guilty"). Conclusion According to findings of the present study, exploring and highlighting the experiences of women with pregnancy termination due to fetal anomalies in the psychological dimension can provide a deeper understanding of the needs of these women for providing optimal care at different times and ultimately promote their psychological health.